A Comparison of the Effectiveness of Cognitive-Behavioral Sexual Skills Training (Masters & Johnson) and Sexual Mindfulness Training on Sexual Satisfaction and Sexual Intimacy in Married Women - Poosti, Marzieh; Amiri, Hassan; Hosseini, Saeedeh Al-Sadat (Mental Health and Lifestyle Journal, 2026)
The present study aimed to compare the effectiveness of cognitive-behavioral sexual skills training (Masters & Johnson) and sexual mindfulness training on sexual satisfaction and sexual intimacy among married women attending healthcare centers in Tehran. The study employed an applied, quasi-experimental research design featuring a pretest-posttest format with a control group and random assignment. The research sample consisted of 45 married women who attended healthcare centers across various regions of Tehran. These participants were selected utilizing a convenience sampling method and were subsequently randomly assigned into three equal groups of 15 participants each: two experimental groups and one control group. At the baseline, all three groups underwent a pretest assessment using the Sexual Satisfaction Questionnaire (Hudson, Harrison, & Crosscup, 1998) and the Sexual Intimacy Questionnaire (Bagarozzi, 2001). Following this, the first experimental group received cognitive-behavioral sexual skills training based on the Masters and Johnson (1996) method, and the second experimental group received sexual mindfulness training (Kocsis et al., 2016). The control group received no intervention during this period. The collected data were processed and analyzed using SPSS version 26. The data analysis indicated that both the cognitive-behavioral sexual skills training (Masters & Johnson) and the sexual mindfulness training exerted a statistically significant positive effect on improving the levels of sexual satisfaction and sexual intimacy among the participating married women ( ). Furthermore, when comparing the comparative efficacy of the two distinct intervention methods, the results demonstrated no significant difference between them concerning their impact on enhancing sexual satisfaction and sexual intimacy. Empowering women through cognitive-behavioral sexual skills and sexual mindfulness training leads to positive and lasting changes in their sexual satisfaction and intimacy, which ultimately enhances overall relationship quality and marital satisfaction.